PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK MELALUI STRATEGI PEMBELAJARAN BERBASIS MASALAH - Kunana Ika Filaili (Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this research was to describe the improvement of short story writing skills of students in class IX-8 SMP Negeri 6 Balikpapan through problem-based learning strategies. The research method used is Classroom Action Research, abbreviated as PTK or Classroom Action Research, a form of research that occurs in the classroom in the form of certain actions taken to improve the teaching and learning process in order to improve learning outcomes better than before. Increasing the score indicates that the implementation of actions in the cycle I and cycle II, were able to improve students' abilities in learning and practice of writing short stories. The application of problem-based learning strategies is also able to provide motivation and pleasure in the Indonesian language learning process, especially writing short stories. Students appear to be more active and more enthusiastic in participating in the short story writing learning process.